THE EXISTENCE OF DALIHAN NA TOLU AS LOCAL WISDOM AND ITS RELEVANCE TO COMMUNITY SOCIAL DYNAMICS: A LITERATURE REVIEW - M. Kharis Majid; Tonny Ilham Prayogo; M. Adib Fuadi Nuriz; Kholid Karomi; Farhah *; Muttaqin *; Nurmala Indah; Rahmat Kausar (Pascasarjana Universitas Hindu Indonesia, 2024)
A local cultural wisdom, which includes various varieties in Indonesia, has its uniqueness which is still maintained today, even though the digital era has become a local community. The rapid development in all aspects of life, from analogue to digital, has made some Batak tribes maintain their local cultural customs, namely Dalihan Na Tolu. Maintaining the existence of Dalihan Na Tolu among local and overseas communities is not easy because to preserve cultural customs, the values of local wisdom experience degradation. The purpose of this study was to determine the activities of Dalihan Na Tolu as a way of life or a philosophy of life for the Batak people because Dalihan Na Tolu is a guideline that has never been abandoned by the Batak people, both locally and overseas. This type of research is library research with qualitative data collection. This research method uses sociology with the subject Dalihan Na Tolu and analysis of social network mapping. To strengthen this method, the researcher uses Clifford Geertz's thought to understand symbols, meanings and identities in Dalihan Na Tolu through a text. This study's findings are that Dalihan Na Tolu's local wisdom has three elements, namely Mora, Kahanggi and Boru. These three elements have interrelated relationships and can facilitate normal societal and cultural activities. Batak people, both local and overseas, can adapt to the situation and developments in this modern era. Thus, the philosophy of Dalihan Na Tolu will never change or disappear, even though times and places are always dynamic.